Dinâmica e mecanismo de ação de metaloenzimas envolvidas na hidrólise de compostos organofosforados - Marcelo Andrade Chagas (2018)
The present PhD thesis involved the theoretical study of the dynamics and reactivity of metalloenzymes involved in the degradation of organophosphate compounds. In particular, the degradation of the phosphate triester paraoxon by the phosphotriesterase enzyme. Initially the nonenzymatic hydrolysis of paraoxon in aqueous solution was studied where it was obtained that, different alkaline hydrolysis, neutral hydrolysis occurs in two stages, through an AN + DN mechanism, with the formation of a pentacoordenado phosphorus intermediate. The reaction exhibits activation free energies of 31.8 and 1.9 kcalmol-1 for the first and second stages, respectively, proceeding through a sequence of proton transfer processes from the nucleophilic water molecule and ending with protonation of the nitrophenolate leaving group. The explicitinclusion of solvation water molecules was essential to describe the proton transfer processes along the reaction coordinate and also to stabilize the pentacoordenated intermediate. The hydrolysis ofparaoxon was also studied using an active site model of the enzyme phosphotriesterase of Pseudomonas diminuta containing Cd2+ ions. From this study a basic mechanism was proposed consisting of: i) Co-ordinate water molecule change and coordination of the substrate to the Cd atom most exposed to the solvent in a monodentate way, ii) protonation of the -hydroxyl bridge ligand by the water molecule and in situ formation of the nucleophile, iii) formation of a pentacoordenate intermediate with significant breaking of chemical bonding of the leaving group and formation of chemical attachment to the nucleophile, iv) protonation of the amino acid residue Asp301 and restoration of the active site by coordination of another water molecule of the solventmedium. It has been shown that the water molecules initially coordinated at the active site play a crucial role in the stabilization of the transition states and the pentacoordinate intermediate. The reaction takes place through a two-step mechanism (AN + DN), with energy barriers of 12.9 and 1.9 kcal mol-1 for the first and second steps, respectively, in excellent agreement with the experimental data. For the enzymatic systems studied, the inclusion of dispersion energy contributes to decreaseenergy barriers by up to 26%. The basic mechanism for the proposed PTE Cd2+/Cd2+ enzyme proved to be a mechanistically consistent and kinetically feasible proposal. The effects of the different metallic cofactors present in the active site of the phosphotriesterase enzyme ofPseudomonas diminuta were evaluated through simulations of Classical Molecular Dynamics. The free ion model and ion model connected with potential parameterization were used for the description of transition metals and parameterization of the force field. The phosphotriesteraseapoenzyme simulations, in relation to the Zn(II)-Zn(II) and Zn(II)-Cd(II) systems, showed that the simple change of one of the metals in the active site, through the RMSF and PCA are already sufficient to provoke and show changes of dynamics in the proteins. Simulations involving thediethyl methylbenzyl phosphate inhibitor and the diethyl p-nitrophenol phosphate substrate were carried out in the Zn(II)-Zn(II) and Cd(II)-Cd(II) parametrized systems. From the results it has been shown that the diethyl methylbenzyl phosphate inhibitor moves from the active site and remains for most of the classical molecular dynamics simulation interacting with amino acid residues from the surface of the enzyme and with the solvent medium in both systems. However, for the substratediethyl p-nitrophenol phosphate we noticed a structural modification and reorientation of the substrate by changing its position in the active site. The results obtained in the PTE simulations indicate that the correlated data in the literature provide information that may not be adequate dueto: i) the energy equilibration of the PTE enzyme system; ii) and the short time of the simulations. Molecular dynamics studies have shown that changes in metal cofactors lead to significant changes in the dynamics of metalloenzymes and therefore affect enzymatic reactivity.